The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-27775-6
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Hybrid Nanoporous Anodic Alumina Photonic Crystals by Heterogeneous Pulse Anodization

Abstract: In this study, we present an advanced nanofabrication approach, so-called ‘heterogeneous pulse anodization’ (HPA), in which galvanostatic stepwise and apodized sinusoidal pulse anodizations are combined in a single process. This novel anodization method enables the precise optical engineering of the characteristic photonic stopbands (PSBs) of nanoporous anodic alumina photonic crystals (NAA-PCs). The resulting structures are hybrid PCs (Hy-NAA-PCs) composed of distributed Bragg reflectors (DBRs) and apodized g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…To provide overview of many functionalities discussed in Sections 4.1-4.7, they are gathered in the Table 2. [190] Gradient-index filters [191] Distributed Bragg reflectors [192] Optical bandpass filters [193] Human protein heavy ions real-time interaction monitoring [194] Tailoring of optical properties with pulse anodization [149] Design of phase shift defect in effective refractive index [195] Hybrid distributed DBRs and apodized GIF photonic structure [196] Characterization of thermotropic ferroelectric liquid crystals confined in the NAA [197][198][199] Glass transition of discotic liquid crystals in one-dimensional fluid [200] Adjustable optical anisotropy by self-assembly of liquid crystals confined in porous structure [201] Sensors NAA template-assisted fabrication of chromium substrate for SERS detection of heavy ions in aqueous solutions [202] Au NPs array on NAA for SERS detection of hemoglobin [203] Controlled fabrication of periodic plasmonic dimer arrays for SERS [204] Graphene-NAA composite for SERS sensing [205] Label-free optical sensor based on interferometric reflectance spectroscopy for TNF-α detection [206] NAA-based interferometer for copper sensing [207] In vivo nanotubes nanotoxicity study on murine model […”
Section: Examples Of Naa Applicationsmentioning
confidence: 99%
“…To provide overview of many functionalities discussed in Sections 4.1-4.7, they are gathered in the Table 2. [190] Gradient-index filters [191] Distributed Bragg reflectors [192] Optical bandpass filters [193] Human protein heavy ions real-time interaction monitoring [194] Tailoring of optical properties with pulse anodization [149] Design of phase shift defect in effective refractive index [195] Hybrid distributed DBRs and apodized GIF photonic structure [196] Characterization of thermotropic ferroelectric liquid crystals confined in the NAA [197][198][199] Glass transition of discotic liquid crystals in one-dimensional fluid [200] Adjustable optical anisotropy by self-assembly of liquid crystals confined in porous structure [201] Sensors NAA template-assisted fabrication of chromium substrate for SERS detection of heavy ions in aqueous solutions [202] Au NPs array on NAA for SERS detection of hemoglobin [203] Controlled fabrication of periodic plasmonic dimer arrays for SERS [204] Graphene-NAA composite for SERS sensing [205] Label-free optical sensor based on interferometric reflectance spectroscopy for TNF-α detection [206] NAA-based interferometer for copper sensing [207] In vivo nanotubes nanotoxicity study on murine model […”
Section: Examples Of Naa Applicationsmentioning
confidence: 99%
“…4 NAA-PCs have distinctive PSBs, the features of which can be readily tuned across the spectral regions by engineering the effective medium of NAA in a multi-dimensional fashion, through various anodization approaches. 45,[47][48][49][50][51][52] These NAA-PC platforms include optical microcavities 47,48 , distributed Bragg reflectors 5 (DBR) 45,49 , linear variable bandpass filters 50 , gradient-index filters 51 , and hybrid PCs 52 . These PC structures provide new opportunities to rationally utilize the "slow photon" effect to attain an efficient management of photons at the nanoscale for photocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission spectra of NAA-GIFs are characterized by a narrow, well-defined, and spectrally tunable PSB, which is a result of a smooth modulation of effective refractive index driven by the SPA profile. Apo-NAA-DBRs and Apo-NAA-GIFs are produced by apodizing STPA and SPA anodization profiles, respectively [ 78 , 79 , 80 , 81 ]. The characteristic PSB of these NAA-PCs is similar to that of their nonapodized counterparts but with much narrower width due to the apodization of their effective medium.…”
Section: Fabrication and Properties: Nanoporous Anodic Alumina As mentioning
confidence: 99%
“…The characteristic PSB of these NAA-PCs is similar to that of their nonapodized counterparts but with much narrower width due to the apodization of their effective medium. Several studies have demonstrated the successful application of different apodization functions to STPA and SPA profiles to engineer the photonic features of NAA-DBRs and NAA-GIFs [ 78 , 79 , 80 , 81 ]. NAA-μCVs are a class of NAA-PCs that confine light to small volumes by resonant recirculation of electromagnetic waves [ 82 , 83 , 84 ].…”
Section: Fabrication and Properties: Nanoporous Anodic Alumina As mentioning
confidence: 99%
See 1 more Smart Citation